Lentil (Lens culinaris Medik.) nodulates with genotypically and phenotypically diverse rhizobia in Ethiopian soils - Tena, W.; Woldemeskel, Endalkachew; Degefu, T.; Walley, F. (Elsevier, 2017)
To determine the symbiotic, phenotypic, and genetic diversity of rhizobia nodulating lentil in Ethiopia, 48 lentil-nodulating rhizobia were isolated from soil samples collected from diverse agro-ecological locations, and characterized based on 76 phenotypic traits. Furthermore, 26 representative strains were selected and characterized using multilocus sequence analyses (MLSA) of core (16S rRNA, recA, atpD, glnIIand gyrB) and symbiotic (nodA and nifH) genes loci. Numerical analysis of phenotypic characteristics showed that the 48 test strainsfell into three major distinct clusters.The evidence obtained from phylogenetic trees based on 16S rRNA genes of the 26 test strains showed that they belong to the Rhizobium genus. Our phylogenetic reconstruction based on combined gene trees (recA,atpDand glnII) supported three distinct sub-lineages (clades I, II and III). Based on thephylogenetic groups constructed from the concatenated genes, strains in genospeciesIand II could be classified with R. etliand R. leguminosarum, respectively. GenospeciesIII, however, might be an unnamed Rhizobium genospecies. Phylogenetic reconstruction based on the symbiosis-related genes supported a single cluster, indicating these genes were highly conserved and suggesting differences in the evolutionary histories of chromosomal and symbiotic genes. Overall, these results confirmed the presence of a great diversity of lentil-nodulatingRhizobium species in Ethiopia, inviting further exploration. Moreover, the differences in symbiotic effectiveness of the test strains indicated the potential for selecting and using them as inoculants to improve the productivity of lentil in the country.